2016
DOI: 10.1186/s40662-016-0051-9
|View full text |Cite
|
Sign up to set email alerts
|

Tear biomarkers for keratoconus

Abstract: Keratoconus is a progressive corneal thinning, ectatic condition, which affects vision. Recent advances in corneal topography measurements has helped advance proper diagnosis of this condition and increased research and clinical interests in the disease etiopathogenesis. Considerable progress has been achieved in understanding the progression of the disease and tear fluid has played a major role in the progress. This review discusses the importance of tear fluid as a source of biomarker for keratoconus and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 67 publications
0
38
0
1
Order By: Relevance
“…10,28,29 Tear mediator profile as a noninvasive biomarker of keratoconus can act as a prognostic biomarker and may aid in the timely treatment of this heterogeneous disease. 6,32,34,46 To the best of our knowledge, there is no longitudinal study evaluating mediators in order to predict the true progression of keratoconus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,28,29 Tear mediator profile as a noninvasive biomarker of keratoconus can act as a prognostic biomarker and may aid in the timely treatment of this heterogeneous disease. 6,32,34,46 To the best of our knowledge, there is no longitudinal study evaluating mediators in order to predict the true progression of keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][10][11][12] Disease specific changes in these molecular markers can be of diagnostic value in keratoconus. 32 To the best of our knowledge, there are no studies examining these mediators in the tear fluid to predict the progression of the disease. However, early detection of progression in keratoconus is of high importance because early identification of the progressive nature of the disease allows early treatment to reduce the risk of visual impairment.…”
mentioning
confidence: 99%
“…Protein levels of PIP and AZGP1 have been found to be down-regulated in tears of KC patients by proteomic analysis, suggesting their application as prognostic markers for KC (Nishtala et al, 2016; Priyadarsini et al, 2014). Our proteomics data also showed that regulation of PIP is closely related to AZGPI glycoprotein of 35–44 kDa (Hassan et al, 2008).…”
Section: Prolactin Induced Proteinmentioning
confidence: 99%
“…The human cornea plays an important role in maintaining the balance of ocular surface microenvironment (Nishtala et al, 2016). Complex array of biomolecules are secreted within the tear fluid, which are potential targets of prognostic value in ocular diseases.…”
Section: Prolactin Induced Proteinmentioning
confidence: 99%
See 1 more Smart Citation